Molecular dynamics simulations of the active matrix metalloproteinase-2: Positioning of the N-terminal fragment and binding of a small peptide substrate - Diaz, Natalia; Suarez, Dimas (Proteins, structure, function, and bioinformatics, 2008)
Herein we use different computational methods to study the structure and energetic stability of the catalytic domain of the active MMP‐2 enzyme considering two different orientations of its N‐terminal coil. The first orientation is largely solvent accessible and corresponds to that observed in the 1CK7 crystal structure of the proenzyme. In the second orientation, the N‐terminal coil is packed against the Ω‐loop and the α3‐helix of the MMP‐2 enzyme likewise in the so‐called “superactivated” form of other MMPs. Binding to the MMP‐2 catalytic domain of a short peptide substrate, which mimics the sequence of the α1 chain of collagen type I, is also examined considering again the two configurations of the N‐terminal coil. All these MMP‐2 models are subject to 20 ns molecular dynamics (MD) simulations followed by MM‐PBSA (Molecular Mechanics Poisson‐Boltzmann Surface Area) calculations. The positioning of the N‐terminal coil in the “superactivated” form is found to be energetically favored for the MMP‐2 enzyme. Moreover, this configuration of the N‐terminal moiety can facilitate the binding of peptide substrates. Globally, the results obtained in this study could be relevant for the structural‐based design of specific MMP inhibitors. Proteins 2008. © 2008 Wiley‐Liss, Inc.